Uso de células-tronco no tratamento de pacientes com miocardiopatia dilatada de diferentes etiologias, associada à ressincronização cardíaca artificial - Greco,Oswaldo Tadeu (2007)
In spite of the development of pharmacological strategies, technology and more sophisticated surgical alternatives, incidences of death from cardiopathies remains high throughout the world, in particular in relation to dilated heart disease. Many of these patients benefit from recent strategies of early myocardial perfusion which significantly reduces mortality rates; even so past-infarction heart failure is common. Recent studies have shown that the infusion of autologous stem cells is a possible treatment to reverse ventricular dysfunction. However, frequently there is an associated electrical conduction defect. Thus, an infusion of stem cells may produce a mechanical correction with heart resynchronization correcting the electrical conduction defect thereby improving the left ventricle ejection fraction. Our institution has been combining stem cell transplantation with resynchronization and, when necessary, cardiofibrilation, to treat these patients giving improvements in the Functional Class, ejection fraction and left ventricle and right ventricle-left ventricle synchrony.